Debt Politics and New Dependencies: A Political Economic Analysis of the Belt and Road Initiative (BRI) in Southeast Asia - Putri, Angelina Aprilia; Zhafirah, Al; Sahide, Ahmad (Magister Ilmu Politik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2025)
This study aims to analyze the dynamics of new debt and dependency politics emerging from China's Belt and Road Initiative (BRI) project in Southeast Asia. The main focus is to see how infrastructure projects funded through the BRI create unequal relations between countries that provide and receive debt. To understand this phenomenon, this study uses an International Political Economy approach with a dependency theory framework from Andre Gunder Frank and other thinkers. This theory views that the relationship between central and peripheral countries in the global system often results in economic and political dependency through debt instruments and structural control. The method used is qualitative descriptive with literature study techniques, including analysis of cases in Laos, Indonesia, and Malaysia. The research findings show that the BRI project not only brings consequences for physical development, but also strengthens China's dominant position fiscally, technologically, and policy-wise in Southeast Asian countries. This dependency indicates the existence of a subordinate reproductive structure in the international system that is disguised through economic cooperation.